Analysis of the Role of Risk Management and Occupational Health and Safety in Preventing Workplace Accidents in the SME Sector Roti Bobby Using the House of Risk (HOR) Method - Syafaat Auladi; Nadia Eka Damayanti; Novi Annisah Ramadhani; Tuwandi Juniarto (SAJMR : Southeast Asian Journal of Management and Research, 2026)
Abstract: This study aims to analyze the role of risk management and occupational health and safety (OHS) in preventing workplace accidents at Roti Bobby MSMEs using the House of Risk (HOR) method. The method used is a quantitative descriptive approach through case studies, with data collection in the form of observation, interviews, and documentation. The analysis was carried out through two HOR stages, namely identification of risk events and risk agents (HOR 1) and determination of priority mitigation strategies (HOR 2). The results showed that there are five main risks, namely injuries from mixer machines, burns from ovens, ergonomic injuries, slips, and product contamination. The dominant risk agents with the highest Aggregate Risk Potential (ARP) values ​​are non-use of personal protective equipment (PPE), absence of standard operating procedures (SOPs), and lack of safety training. Priority mitigation strategies include mandatory implementation of PPE, preparation of SOPs, and implementation of periodic OHS training. These findings indicate that managerial and behavioral factors are more influential than technical factors in causing workplace accidents. The HOR method has proven effective in identifying and prioritizing risks and producing applicable mitigation strategies for MSMEs. Keywords: Risk Management, Occupational Health and Safety, House of Risk, MSMEs, Risk Mitigation